Ground-Penetrating Radar Evaluation of Moisture and Frost across Typical Saskatchewan Road Soils - Curtis Berthelot; Diana Podborochynski; Timo Saarenketo; Brent Marjerison; Colin Prang (Advances in Civil Engineering)
This study was undertaken to evaluate the effect of soil type, moisture content, and the presence of frost on road substructure permittivity. Permittivity sensitivity of typical road soils was characterized in the laboratory to provide baseline dielectric constant values which were compared to field ground penetrating radar (GPR) survey results. Both laboratory devices, the complex dielectric network analyzer and the Adek Percometer, as well as the field GPR system were used in this study to measure the dielectric constant of soils. All three systems differentiated between coarse-grained and fine grained soils. In addition, at temperatures below freezing, all three systems identified an increase in water content in soils; however, when frozen, the sensitivity of dielectric constant across soil type and moisture content was significantly reduced. Based on the findings of this study, GPR technology has the ability to characterize in situ substructure soil type and moisture content of typical Saskatchewan road substructure soils. Given the influence of road soil type and moisture content on in-service road performance, this ability could provide road engineers with accurate estimates of in situ structural condition of road structures for preservation and rehabilitation planning and optimization purposes.